A quantum dynamics study of the hyperfluorescence mechanism. Issue 4 (5th January 2021) - Giret, Yvelin; Eng, Julien; Pope, Thomas; Penfold, Thomas
Abstract : Triplet state harvesting using thermally-activated delayed fluorescence (TADF) combined with efficient Förster resonant energy transfer (FRET) is studied using quantum dynamics to understand the key properties controlling the hyperfluorescence mechanism in 4th generation organic light-emitting diodes (OLEDs). Abstract : Triplet state harvesting using thermally-activated delayed fluorescence (TADF) combined with efficient Förster resonant energy transfer (FRET) to a narrow fluorescent emitter is seen as a promising approach to achieve high efficiency and colour-purity in organic light-emitting diodes (OLEDs). In this work, we perform quantum chemistry and quantum dynamics simulations to model the so-called hyperfluorescence (HF) process between a carbene–metal–amide (CMA) molecule with a Au bridging metal (Au-Cz ) and a narrow blue fluorescent emitter, 2, 5, 8, 11-tetra- tert -butylperylene (TBPe). Our quantum dynamics simulations illustrate a FRET rate of ∼10 10 s −1 indicating that it occurs on the picosecond timescale comparable with the ISC crossing rate of Au-Cz . This high FRET rate, which is most strongly dependent on the energy difference between the S1 states of the donor and acceptor molecules, is advantageous for devices as it encourages rapid triplet harvesting. In addition, the comparable FRET and intersystem crossing (ISC) rates, in contrast to most organic only systems, would facilitate studying this mechanism using photoexcitation. Besides the FRET rate, Förster radii are also estimated from the quantum dynamics simulations for different energy differences between the donor and acceptor molecules and are in quantitative agreement with the experimental estimations for different systems, showing that quantum nuclear dynamics simulation could be an important tool for enhancing our understanding of hyperfluorescence-based emitters.